FACTOR RELATED TO PERFORMANCE OF PAPRINGAN BATIK WORKERS, BANYUMAS REGENCY DURING THE COVID-19 PANDEMIC - Damairia Hayu Parmasari; Suryanto; Nur Ulfah; Heryanto (The Indonesian Journal of Public Health, 2023)
Introduction: The COVID-19 pandemic has an impact on various sectors including small medium enterprise. One of the small medium enterprises affected by the COVID-19 pandemic is Batik Papringan in Banyumas Regency. The decline in income due to the pandemic caused batik to experience a decline in performance. The decline in performance also had an impact on the amount of batik and the income generated. Aims: to determine the factors related to the performance of Batik Papringan Workers in Banyumas Regency. Methods: The research was conducted with a sample of 48 batik workers. The instrument is questionnaire. The questionnaire in this research is a self-developed questionnaire which was developed from a validated and reliable questionnaire. The analysis was performed using chi-square to examine the relationship between the 2 variables and logistic regression to determine the factors most associated with performance. Result: The results showed that in the bivariate test, age and work satisfaction were factors related to performance, while in the multivariate test the most related factors were work satisfaction. The p value of the relationship between work satisfaction and performance is 0.049. Conclusion: The conclusion of this study work satisfaction is the factor most related to the performance of batik makers that needs to be improved. The solution that can be done is to apply strategies and tricks in marketing batik products to consumers so that consumers are more interested in buying batik. The more batik is sold, the more worker satisfaction increases.